Lecture on-line/on-demand / Foo Siew Ping - Foo, Siew Ping (2001)
The on-line/on-demand lecture broadcasting is an ideal approach to meet the demand of effective and efficient communication for the fast growing web and multimedia technology. Thus, this project, the development of Lecture On-Line/On-Demand (LOL/LOD) broadcasting system provides the common functional components required for broadcasting both real time and not real time lectures. This will have resolved some existing education delivery bottlenecks such as time inconvenience, location dependence, space and tools limitation in the existing systems.Furthermore, there are viewer and administrator modules proposed for the LOL/LOD system. The viewer section allows the user to view, sort, search on-line or on-demand lectures and e-mail to lecturer with the click-and-reply hyperlink feature. Meanwhile, the administrator can literally edit, sort, search lectures and upload new teaching materials to the database. All these functions are offered via web pages. The LOL/LOD system is mainly developed using the Active Server Pages (ASP), VBScripts as the web programming language and Internet Information Server 4.0 as web server under the Windows 2000/NT Server environment. Moreover, the lecture information and teaching materials will be kept in the Microsoft SQL Server 7.0 and retrieved via the Open Database Connectivity database access middleware. Besides the streaming multicast and unicast will be the lecture broadcasting technologies used in this system. Also, the Windows Media Technology is employed in the system to support the multicast and unicast streaming. Although there were problems encountered during the system development, the final system built meets both the functional and non-functional system requirements successfully, Besides, the objectives of the project also had reasonably been achieved. Thus, the LOL/LOD system can be served as a fundamental model important for future enhancement and development.